Aktualisasi Nilai-Nilai Kristiani dalam Menjunjung Tinggi Moderasi Beragama di Tengah Masyarakat Majemuk - Aprilius Nahak; Vanbe Toven Hulu; Kometa Sihombing; Rentinawati Siahaan; Viktor Deni Siregar; Moralman Gulo (Jurnal Filsafat dan Teologi Katolik, 2025)
Religious moderation in Indonesia, especially in a pluralistic society, has diversity, ethnicity, race and culture. Thus, conflicts often occur in these differences, resulting in differences of opinion and not being able to accept opinions between religions, in the end there was the burning of houses of worship and such debates. With the context of religious moderation as Christians, it teaches about loving fellow human beings even though they have different beliefs. Therefore, researchers provide an overview and support for maintaining each other's good name, harmony and tolerance between religions in Indonesia. The method used is a qualitative and descriptive method with a library approach and collecting data regarding religious moderation, then analyzing and emphasizing arguments and then drawing conclusions as a result of the study conducted. The results of the discussion are where religious people must be humble, love each other even though they have different religions.